2016
DOI: 10.1177/1468798415608907
|View full text |Cite
|
Sign up to set email alerts
|

The impact of book reading in the early years on parent–child language interaction

Abstract: Early language development predicts later reading competence, but does reading to young children enhance the language interaction between them and their parents? Automatic assessment of language interaction now yields Adult Word Counts (AWC), Conversational Turn counts (CT) and Child Vocalization counts (CV). This study had 98 families return reading activity logs for a day coinciding with automatic language analysis, and of these 36 reported reading with their children aged 26-61 months on that day. Reading p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 34 publications
0
48
2
1
Order By: Relevance
“…In addition to the three vocal coordination patterns that have been the foci of this study, for this section, we also included a conversational turn‐taking measure computed by the LENA system. The conversational turn‐taking measure computed by LENA is frequently used in the literature (Caskey, Stephens, Tucker, & Vohr, ; Gilkerson & Richards, ; Gilkerson, Richards, & Topping, ; Greenwood et al., ; Suskind et al., ; Warren et al., ) and is therefore an important measure to include when assessing independent associations with infant age. A conversational turn is identified when a sequence of speech‐related sound segments from an adult then an infant, or vice versa, occurs within 5 sec without an intervening non‐speech‐related segment or speech‐related segment from another adult or infant.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the three vocal coordination patterns that have been the foci of this study, for this section, we also included a conversational turn‐taking measure computed by the LENA system. The conversational turn‐taking measure computed by LENA is frequently used in the literature (Caskey, Stephens, Tucker, & Vohr, ; Gilkerson & Richards, ; Gilkerson, Richards, & Topping, ; Greenwood et al., ; Suskind et al., ; Warren et al., ) and is therefore an important measure to include when assessing independent associations with infant age. A conversational turn is identified when a sequence of speech‐related sound segments from an adult then an infant, or vice versa, occurs within 5 sec without an intervening non‐speech‐related segment or speech‐related segment from another adult or infant.…”
Section: Resultsmentioning
confidence: 99%
“…(), who compared vocabulary diversity in the text of common children's books to vocabulary diversity in parent speech in CHILDES. Another recent study using parent‐reported activity logs showed that book‐reading interactions include a higher number of conversational turns and parent word count compared to non‐book interactions (Gilkerson, Richards, & Topping, ). Our unique contribution is that because of the nature of our data, which consisted of naturalistic parent–child interactions, we also were able to examine parent language around book reading (e.g., extending the topic, describing the pictures), not just their reading of the text of the books.…”
Section: Discussionmentioning
confidence: 99%
“…This would also allow for the measurement of the number of conversational turns between the DLP wearer and other adults and the amount of speech produced by the DLP wearer and other adults in a conversation, which would help to assess relative social participation. These variables have provided important insights into children’s patterns of verbal behavior in natural settings (e.g., VanDam et al, 2012; Thiemann-Bourque et al, 2014; Gilkerson et al, 2015; Sosa, 2016). Optimizing the LENA algorithms for use with adult DLP wearers could provide researchers and clinicians with a better understanding of the auditory environments and communication patterns of adults, as well as the real-world effects of intervention on the lives of adults.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the LENA system provides access to detailed second-by-second data of sound levels and auditory environment classification, which allows for in-depth data mining. LENA was designed for and has been used extensively to study the language-learning environments of children (e.g., VanDam et al, 2012; Thiemann-Bourque et al, 2014; Gilkerson et al, 2015; Sosa, 2016), but it has also been used with adults (Li et al, 2014). Specifically, Li et al asked 37 older adults (aged 64–91 yr) residing in a retirement community to wear a LENA DLP for one day.…”
Section: Introductionmentioning
confidence: 99%